Analisis Kepatuhan Minum Obat dan Outcome Terapi pada Pasien Hipertensi di Puskesmas Se-Kabupaten Bengkalis : Analysis of Medication Adherence and Therapeutic Outcome in Hypertension Patients at Public Health Centers in Bengkalis Regency - Husnawati - Husnawati; Syilfia Hasti; Rizki Abi Rahman (JURNAL FARMASI DAN MAKANAN, 2025)
Hypertension is a chronic disease and cannot be cured, but it can be controlled. One of the determining factors for the success of hypertension treatment is medication adherence to avoid complications. The level of adherence to antihypertensive varies among patients. The aim of this study is to analyze medication adherence and therapeutic outcome in hypertensive patients at health centers throughout Bengkalis Regency. This observational study uses a cross-sectional design with a descriptive-analytic method. The sample in this study consisted of 120 respondents who met the inclusion criteria, and the sampling technique was conducted using non-probability purposive sampling. This study was conducted at health centers across Bengkalis Regency, with five health centers serving as data collection sites. Based on this study, it was found that the majority of respondents (43.3%) had low adherence and only 37.5% achieved desired outcome. Based on the results of the Chi-Square test, it can be concluded that there is a relationship between medication adherence and therapeutic outcome in hypertensive patients at health centers throughout Bengkalis Regency, with a p-value of 0.001.